Antioxidant activity of scleroglucans from Sclerotium rolfsii ATCC 201126 - Viñarta, Silvana Carolina (2011)
Carbohydrate polymers have been reported to modulate in vitro and in vivo inflammatory responses. Beta-D-(1,3)-glucans, such as scleroglucan, may possess free radical scavenging activity. If glucans are free radical scavengers then, it might partly explain the ability of these ligands to modulate inflammatory responses. In the present work, the free radical scavenging activity of lab-fermenter scale produced scleroglucans from the filamentous fungus S. rolfsii ATCC 201126 (EPS I, EPS II and EPSi) and a commercial scleroglucan (LSCL) was examined. The study involved the use of the phycoerythrin/AAPH fluorescence assay based on the method of Glazer. The antioxidant properties of both triple and single helix scleroglucan conformations were also compared. The oxygen radical absorbance ability of these carbohydrate polymers in aqueous medium was compared and contrasted with commercial antioxidant agents (PDTC and Trolox). As a general rule, single helix conformation showed greater antioxidant ability than triple helix. With the exception of LSCL, all scleroglucans treated with 0.2 N NaOH (corresponding to the single helix conformation) exhibited a variable degree of free radical scavenging activity (EPS I < EPSi < EPS II), and the antioxidant effect was concentration-dependent (optimal at 0.25 µg/mL). The lower values of EC50 (the dose that corresponds to a 50% antioxidant ability) exhibited by alkali-treated samples allowed to confirm their marked antioxidant activity (EC50 = 121-194 µg/mL). EPS I single helix conformation showed an antioxidant activity comparable to PDTC (equivalent to ~84%) and superior to Trolox (~160%). Meanwhile, the EC50 values obtained for native samples (EC50 = 805-5920 µg/mL) denoted the weak free radical scavenging activity exhibited by triple helix. Polysaccharide antioxidant effects have been already correlated with the monosaccharide composition. However, polymers are significantly better free radical scavengers than either of the monosaccharides. This fact would indicate that the polymeric structure confers additional free radical scavenging ability. According to our results, the antioxidant activity herein demonstrated for scleroglucans from S. rolfsii could be not only a consequence of their glycosidic composition but also a property associated to the conformational state of the polysaccharide. The demonstrated antioxidant ability would represent a further contribution to the great biological potential of the produced fungal polysaccharides.